A new evaluation method to quantify the wear failure of irregular cutting tool during shield TBM tunneling in abrasive sandy ground. (April 2023) - Tang, Shao-Hui; Zhang, Xiao-Ping; Xie, Wei-Qiang; Liu, Quan-Sheng; Wu, Jian; Chen, Peng
Highlights: 3D laser scanning technology is used to reconstruct irregular cutting tool model. Dimensionless parameters are proposed to quantify irregular cutting tool wear. 3D quantitative method is developed to rationally evaluate tool wear failure. Heterogeneous wear and eccentric wear are analyzed by 3D quantitative method. Abstract: When shield TBM tunneling in abrasive sandy ground, excessive cutting tool wear resulting from untimely and inaccurate failure evaluation is prone to damage cutterhead structure and delay tunneling progress. Hence it is critical important for fast and accurate evaluation of tool wear failure. At present, caliper measurement method is used to qualify cutting tool wear in abrasive ground tunneling. The height reduction of cutter edge is considered as a common parameter to evaluate whether cutting tool is invalid. When it comes to irregular cutting tool, they will be unsuitable due to the complex surface topography. Especially when abrasive sand remains between the cutterhead and excavation face, severe secondary wear will occur on cutter body instead of cutter edge. There is still a lack of comprehensive methods and parameters for evaluating the wear failure of cutting tools. In the present study, the handheld 3D laser scanner has been applied to obtain the point cloud data of irregular cutting tool. The point cloud data has been imported into the Geomagic Control software for model reconstruction. Then, surface overlapped methodology has been utilized for the comparison of cutting tool models before and after wear to obtain the 3D wear nephogram. Cutter volume wear ratio ( CVWR ) and cutter height wear ratio ( CHWR ) have been proposed to quantity the wear failure of cutter edge and cutter body. A case study of ripper tooth and replaceable scraper at Sutong GIL Yangtze River Crossing Cable Tunnel has been conducted to set the threshold value of wear failure. The results indicate that the CVWR and CHWR are functional to identify the wear failure of irregular cutting tools. Compared with traditional caliper measurement method, 3D quantitative method allows a more rational and accurate evaluation of heterogeneous cutter edge wear and eccentric cutter body wear.